New Collectivization in the Age of Discipline Domination; Review of the Book of Sociology of Modernity, Liberty, and Discipline - Farzad Azarkamand (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book of “Sociology of Modernity, Liberty and Discipline” presents a historical-sociological narrative of Western modernity. In this book, different types of modernity - Western Europe, Soviet Socialism, and Western America - have been studied with a historical approach. The writer of the work believes that modern institutions are in conflict with freedom and discipline, and sociology is nothing more than a description of modernity, freedom, and discipline. This means that modernity, in contrast to what initially showed itself as an individual and social freedom, took on a restrictive and disciplinary character. According to the author, the most important features of modernity are the passage from a free society to the disciplinary community and the rule of discipline for the formation of the political society. The dual nature of modernism and the domination of discipline and the restriction of individual and social freedoms at the foot of the rationality of modernism have eliminated the dream of achieving true freedom. The author’s suggestion is that the new collectivization and the formation of transitional congregations could be considered a way to get rid of the discipline of modernity.